EVALUATION OF SCOUT EXTRACURRICULAR PROGRAMS IN VOCATIONAL SCHOOLS USING THE CIPP MODEL - Yosi Nofita Sari; Rofi Chandra; Ambiyar; Fahmi Rizal (Jurnal Mantik, 2022)
The purpose of this research is to analyze the scout extracurricular program at SMKS Dhuafa Padang because the program has not been evaluated in a long time. The goal of this study was to see how the CIPP (Context, Input, Process, Product) assessment methodology might be used to evaluate the scout extracurricular program at SMKS Dhuafa Padang. This study employs the CIPP model to assess context components, inputs, processes, and products in order to develop a strong and successful scout extracurricular program. The principal and scout coach of SMKS Dhuafa Padang provided the data for this study. Observation, interviewing, and documenting approaches were used to obtain data. The information that has been gathered is subsequently put to use.